2022
DOI: 10.3389/fchem.2022.1005231
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of highly fluorescent carbon dots as fluorescence sensors for the parallel detection of cadmium and mercury ions

Abstract: Cadmium (Cd2+) and mercury ions (Hg2+) are essential for the quality control of food samples because of their serious toxicity to human health, but the effective and simple strategy for their parallel detection remains challenging. In this paper, a rapid and simple parallel detection method for Cd2+ and Hg2+ was developed using carbon dots (CDs) as fluorescent sensors. A one-step hydrothermal method with a single precursor l-arginine as both the carbon and nitrogen sources was employed to prepare nitrogen-dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…While, the peaks associated around 1416 cm −1 , 1118 cm −1 and 1010 cm −1 are typical for stretching vibrations of C−O bond in carboxylic group, C−O−C bond and C−N stretching vibration respectively. Moreover, the peak position at 618 cm −1 , indicates the presence of out of plane vibration of C−H group as reported in the previous literature [32,33] . However, it is observed that the peaks are more intense in case of CD2 than its counterpart CD1.…”
Section: Resultssupporting
confidence: 77%
“…While, the peaks associated around 1416 cm −1 , 1118 cm −1 and 1010 cm −1 are typical for stretching vibrations of C−O bond in carboxylic group, C−O−C bond and C−N stretching vibration respectively. Moreover, the peak position at 618 cm −1 , indicates the presence of out of plane vibration of C−H group as reported in the previous literature [32,33] . However, it is observed that the peaks are more intense in case of CD2 than its counterpart CD1.…”
Section: Resultssupporting
confidence: 77%
“…This phenomenon may be attributed to the chelating effect between the surface functional groups of carbon dots and metal ions. Based on IR spectroscopy, chelate complexes can be presumably formed with −NH/NH 2 , −CO, and −OH groups, where nitrogen and oxygen atoms can donate lone pairs to the unoccupied orbitals of metal ions . Furthermore, a detailed investigation of the absorption spectra suggests that for the Co 2+ ion, an additional quenching mechanism should be considered, namely, the inner filter effect (IFE), stemming from a partial overlap between the Co 2+ absorption spectrum and the CD’s emission spectrum at 530 nm. , …”
Section: Resultsmentioning
confidence: 99%
“…49 Furthermore, a detailed investigation of the absorption spectra suggests that for the Co 2+ ion, an additional quenching mechanism should be considered, namely, the inner filter effect (IFE), stemming from a partial overlap between the Co 2+ absorption spectrum and the CD's emission spectrum at 530 nm. 49,50 The absorption spectra were analyzed in various solvents, including protic solvents such as water and EtOH (ethanol) and the aprotic solvent DMSO (dimethyl sulfoxide) (Figure S5). Across this solvent series, the band gap slightly decreased, which might indicate the formation of hydrogen bonds between the solvent molecules and functional groups on the CDs' surface.…”
Section: Lifetime Response Of Cds Interacting With Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since uorescent carbon dots (CDs) have advantages such as low toxicity, good biological compatibility, good water solubility, and high photo-stability, their application value in heavy metal detection has naturally received widespread attention. [51][52][53][54] Functionalized CDs, especially those with surfaces rich in carboxyl, sulydryl, amino groups and so on, are easily combined with heavy metals differently, usually resulting in non-uorescent complexes, and the uorescence quenching mechanism is mainly involved in static quenching. Wu et al 55 had synthesized nitrogen-doped carbon quantum dots (N-CQDs) by a microwave hydrothermal method using citric acid and urea as sources (Fig.…”
Section: Fluorescent Sensor Based On the Static Quenching Mechanismmentioning
confidence: 99%